IDENTIFIKASI POTENSI “PASIRAMAN PURA DALEM PINGIT LAN PURA KUSTI” DI DESA SEBATU, GIANYAR SEBAGAI WISATA SPIRITUAL - Okayana, I Gusti Agung Putu Agus; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA, 2015)
ABSTRACT The background of this research is the condition of “Pesiraman Pura Dalem Pingit lan Pura Kusti” which is still undeveloped as tourism attraction , despite the increasing number of visitors each year. The purpose is to describe the potential of “Pesiraman Pura Dalem Pingit lan Pura Kusti” which could be used to develop tourism. Therefore the main discussion will be the potentials identification of “Pesiraman Pura Dalem Pingit lan Pura Kusti” as spiritual tourism and the opinion of the locals to the “Pesiraman Pura Dalem Pingit lan Pura Kusti” development as a tourism destination. The potentials is separated into two, which is physicals and non-physicals. The physicals is described using Cooper’s 4A which the main potentials categorized into attractions, while the supporting potentials into accessibility, amenities, and ancillary. The non-physicals is local’s culture, and supported by their human resource, categorized into profession, capabilities, education, health, and density. The method on choosing the source persons is using the cluster random sampling; the locals will be categorized into clusters, which is, farmers, entrepreneurs, employees, and civil servants. From each clusters is taken 2% and resulting 10 source persons. The data collecting is done by doing short interview.
Keywords: Potential Identification, attractions, Spiritual tourism.